Ascetic worshipping the Linga - Temples of India Project Team (Jio Institute, 2024)
The pillars in the manḍapa of the Harsha Temple are enriched with beautiful images of apsaras and female deities like Parvati (as depicted in this image) in the niches of the pillars. These female figurines correspond to the plethora of female figurines (Parvati and damsels) depicted inside the sanctum on the walls. Beneath these pillar niches are panels depicting musicians, dancers, celestial beings, deities like Ganesha and ascetics. These Shaiva ascetics align with the overall Shaiva theme of the temple. The depicted image shows an ascetic worshipping the shivalinga. The four-armed Parvati is holding a kamandalu and mala in her lower hands and likely flowers in the upper two. On either side of her are attendant dwarfs. The ascetic shown in the panel below, with long matted hairs, is shown in deep adoration to Shiva.